Private investigator - Goldberg, Jan. (Mankato, Minn. : Capstone High/Low Books, 1999)
Describes the necessary training, job responsibilities, work environment, salaries, and job outlook for private investigators. Provides addresses for contact information.
Includes bibliographical references (p. 45) and index.
Keywords: Private investigators -- United States -- Juvenile literature; Private investigators -- Juvenile literature. -- United States -- Juvenile literature; Detectives -- Vocational guidance; Vocational guidance